427 Comparison of PAP Interface Pressure on the Nasal Bridge: Soft Cloth vs. Traditional Masks. (3rd May 2021) - Anastasi, Matthew; Pasquale, Maria; Tubbs, Andrew
Abstract: Introduction: Pressure between a CPAP mask and the skin is a significant contributor to irritation and pressure ulcers, an area of localized soft tissue ischemic necrosis caused by prolonged pressure over bony prominences that exceeds supra capillary pressure (70 mmHg). We hypothesized that cloth masks (CM) would exert a lower nasal bridge pressure than traditional mask (TM) products constructed of silicone and plastic. Methods: We evaluated the pressure exerted by seven types of nasal masks in three trials onto the nasal bridge of two healthy adult volunteers, one female, one male, while they received 10 cm H₂O of CPAP. Five commercially available CMs (SleepWeaver® 3D, SleepWeaver® Advance Pediatric, SleepWeaver® Élan, and SleepWeaver® Prevent, Circadiance®, LLC) were tested as were three TMs constructed primarily of silicone and plastic (DreamWisp™, Philips Respironics, Inc.; Mirage™, ResMed; Zest™, Fisher & Paykel Healthcare). Pressure was detected using a texsens®-g low pressure sensor force measuring device. Pressure data from each 30 second trial were summarized as the median value after confirming that pressure did not vary by time (one-way ANOVA, p = 0.7393). Median values were then compared across trials, subjects, and masks using one-way ANOVAs and student's t-tests. Results: After confirming that pressure did not vary by trial (one-way ANOVA, p=0.4585) or subject (t-test, p=0.0938), pressure data were summarized by mask. On average, CMs exerted 37.0 (17.7) mmHg of nasal bridge pressure, although there was significant variation across masks (one-way ANOVA, p < 0.0001). Conversely, TMs averaged 112 (38.5) mmHg of nasal bridge pressure without significant variation across masks (one-way ANOVA, p=0.1291). CMs averaged 75.26 mmHg less pressure than TMs (p < 0.0001), a difference of 67 percent. Conclusion: The data supports the hypothesis that pressure from CMs on the bridge of the nose are significantly lower than a sample of TMs with similar shape and style, and the null hypothesis was rejected. Furthermore, the average CM was below the threshold for capillary closing, in contrast to the average TM. Therefore, for CPAP users with predicted or existing skin sensitivity, comfort and/or compliance concerns, CM should be considered as a first choice in mask selection. Support (if any):